2022
DOI: 10.21037/atm-22-6049
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-induced PD-L1 expression in tumor and its microenvironment facilitates cancer-immune escape: a narrative review

Abstract: Background and Objective: Radiotherapy (RT) is one of the fundamental anti-cancer regimens by means of inducing in situ tumor vaccination and driving a systemic anti-tumor immune response. It can affect the tumor microenvironment (TME) components consisting of blood vessels, immunocytes, fibroblasts, and extracellular matrix (ECM), and might subsequently suppress anti-tumor immunity through expression of molecules such as programmed death ligand-1 (PD-L1). Immune checkpoint inhibitors (ICIs), especially anti-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 149 publications
(164 reference statements)
0
8
2
Order By: Relevance
“…The intrinsic PD-L1 expression in surviving cells remained unaffected by irradiation across all cell lines ( Figure 1B ). This observation contradicts findings from other preclinical research, such as those conducted by Wang ( 36 ) or Deng and colleagues ( 16 ), who reported an increased PD-L1 expression upon irradiation in mouse mammary tumor models (BALB/c, C57BL/6). However, our data align with observations made in clinical settings ( 37 ).…”
Section: Discussioncontrasting
confidence: 96%
“…The intrinsic PD-L1 expression in surviving cells remained unaffected by irradiation across all cell lines ( Figure 1B ). This observation contradicts findings from other preclinical research, such as those conducted by Wang ( 36 ) or Deng and colleagues ( 16 ), who reported an increased PD-L1 expression upon irradiation in mouse mammary tumor models (BALB/c, C57BL/6). However, our data align with observations made in clinical settings ( 37 ).…”
Section: Discussioncontrasting
confidence: 96%
“…However, the data did not include a neoadjuvant treatment modality inclusive of radiotherapy. Emerging data on the cellular effects of radiotherapy in the treatment of solid tumors has demonstrated upregulation of PD-L1 receptor expression on tumor cells as well as within the tumor microenvironment 16 . This suggests that there may be a synergistic mechanism in terms of anti-tumor effect following a neoadjuvant chemoRT+I/O in esophageal cancer.…”
Section: Resultsmentioning
confidence: 99%
“…Shao and colleagues reported that IR (4 Gy) significantly increased the m 6 A levels in several colorectal cancer cells, probably due to the reduced m 6 A eraser ALKBH5 after IR ( Shao et al, 2023 ). A recent report noted that IR increases m 6 A reader YTHDF2 in MDSCs both in vitro (4 Gy) and in vivo (one dose of 20 Gy) ( Wang et al, 2022 , 2023a ). These data suggest that IR-mediated alterations in expression of m 6 A proteins may impact anti-tumor efficacy.…”
Section: The Crucial Signaling Pathways Activated By Ir or Ir+immune ...mentioning
confidence: 99%
“…Increasing evidence has demonstrated that radiation induces an increase in expression of PD-L1 on tumor cells in multiple cancers including colon, head and neck, squamous cell carcinoma, breast cancer, nasopharyngeal carcinoma, prostate cancer, and glioma ( Chen et al, 2023b ; Ding et al, 2020 ; Dovedi et al, 2014 ; Oweida et al, 2017 ; Wu et al, 2016 ). Radiation induces PD-L1 expression in tumor cells via various pathways like DNA damage/ATM/STAT3/IRF3 axis, IFN-γ/JAK/STAT/PD-L1 pathway, cGAS-STING signaling, epidermal growth factor receptor (EGFR)/PI3K-AKT cascade, and the HIF-1α signaling ( Ding et al, 2021 ; Wang et al, 2022 ). Of note, other signaling pathways may be involved in the regulation of PD-L1 expression in tumors.…”
Section: The Crucial Signaling Pathways Activated By Ir or Ir+immune ...mentioning
confidence: 99%